Self Enterpreneurship Learning to Increasing Teacher Creativity Using Merdeka Belajar Platform - Ridwan Ridwan (Institut Agama Islam Negeri Palopo, 2023)
Teacher creativity in strengthening the value of entrepreneurial character so that creativity can be seen from planning, implementation and assessment of learning. Research was conducted on high school teachers in Langsa City. By utilizing the geographical richness of the school environment as a learning resource in applying character values (entrepreneurship) which are integrated in the development of teaching tools by teachers and also in preparing school programs related to the importance of learning innovation for students. Using qualitative descriptive methods, intervention activities were carried out on 5 high school teachers. Activities are divided into three, namely pre-meeting, meeting and post-meeting. At the pre-meeting, assignments were given to teachers regarding the use of the Merdeka Belajar platform, qualitative descriptive research carried out in the even semester using instruments such as observation sheets, interviews and analysis documents. The results of the data analysis show that the increase in teacher creativity in applying integrated entrepreneurial values in subjects, managing learning activities, giving assignments and assessments is character-based